A localized sand erosion prediction approach for multiphase flow in wells: application for sudden-expansions. (17th November 2021) - Darihaki, Farzin; Hajidavalloo, Ebrahim; Ghasemzadeh, Amir; Safian, Gholam Abbas
Abstract: The present study aims at finding the severity of the erosional damage for sudden-expansion geometries in a candidate oil well. A two-step approach is proposed for the localized erosion prediction in wells. At first, one-dimensional flow through the well strings is solved using the transient multiphase flow simulator, OLGA, which provides phase properties and flow conditions for the local erosion calculation. Then, the recorded flow data are employed for a detailed three-dimensional computational fluid dynamics (CFD)-based flow and erosion calculation in the selected sections of the well. In this study, two sudden-expansion geometries at substantially different depths are selected and investigated. Erosion magnitude and its pattern are evaluated for multiphase flow conditions and compared with single-phase flow. It is found that the erosional damage for the multiphase flow could be because of the random impingements due to the pipe size effect on the multiphase flow regime which is an indirect effect of the flow transition through sudden-expansion. The most severe condition is encountered for the expansion geometry closer to the wellhead, but the annual erosion rate is below the critical rate. However, for the dry-gas wells when a liquid film is not present, the erosion rate could be significantly above the critical rate.